(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. In recent years, cataract surgery is a widely used method of femtosecond laser cataract extraction, which is most effective in patients with I-III degree of lens density by Buratto classification. Therefore, it is important to make preoperative diagnosis of mechanical properties of the lens for differential selection of patients who are planned to perform femtosecond laser cataract extraction. Purpose. To develop a method for determining the lens density characteristics obtained from the index of relative acoustic resistance in patients with age-related cataract using ultrasound (US) — B Scanning to select the optimal surgical treatment. Material and methods. 51 patients with age-related cataract were performed surgery — cataract phacoemulsification with intraocular lens implantation (YUL) (64 eyes). All patients were made digital ultrasound scanning of the lens on the device «CineScan» with determination of acoustic echogenicity in different layers of the lens and using advanced methods index relative acoustic resistance in different layers of the lens was specified. Results. The study has found that there is a direct correlation between the relative acoustic resistance specified before the operation and the rate of cumulative disparate energy, which can be determined after the operation in each case (Pearson’s coefficient 0.78). Conclusions. The use of the improved method for determining the density of the lens characteristics revealed a direct correlation between the relative acoustic resistance determined before surgery and the rate of cumulative disparate energy. These data objectively allow to distinguish patients of I-III degree of lens density for femtosecond laser cataract extraction.